The Caryotipe of Endemic Ornamental Fish Celebes Rainbow (Telmatherina ladigesi) from Maros River, South Sulawesi - Andriani, I.; Sugiri, N.; Carman, Odang; Sjafei, D.S. (Indonesian Society of Scientific Aquaculture (ISSA), 2004)
The objective of this research was to find the caryotype of the endemic ornamental fish, Celebes rainbow (Telmatherina ladigesi) from Maros River South Sulawesi, Indonesia. The experimental fish were caught from the branches of Maros River, those are Bantimurung River, Pattunuangasue River and Makkatoang River. Tissue collection and slide preparation were carried out using the solid tissue technique with slight modification. The amount of chromosome pairs found from those three rivers (three population) were 2n = 48. These chromosomes were divided into 13 pairs big chromosomes (>1 urn) and 11 pairs small chromosomes (I u,m) dan 11 pasang kromosom kecil (